2012
DOI: 10.3945/ajcn.111.026286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a tomato-rich diet on markers of cardiovascular disease risk in moderately overweight, disease-free, middle-aged adults: a randomized controlled trial

Abstract: These data indicate that a relatively high daily consumption of tomato-based products (equivalent to 32-50 mg lycopene/d) or lycopene supplements (10 mg/d) is ineffective at reducing conventional CVD risk markers in moderately overweight, healthy, middle-aged individuals. This trial was registered at isrctn.org as ISRCTN34203810.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
3
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(120 citation statements)
references
References 46 publications
1
108
3
2
Order By: Relevance
“…Moreover, this decrease was evident in spite of high-sensitivity C-reactive protein, interleukin-6, intercellular adhesion molecule and vascular cell adhesion molecule not being affected in this cohort [28], suggesting that SAA may be a sensitive marker to identify inflammatory changes related to adiposity. It is known that SAA positively correlates with BMI and is released by hypertrophic adipocytes [2].…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, this decrease was evident in spite of high-sensitivity C-reactive protein, interleukin-6, intercellular adhesion molecule and vascular cell adhesion molecule not being affected in this cohort [28], suggesting that SAA may be a sensitive marker to identify inflammatory changes related to adiposity. It is known that SAA positively correlates with BMI and is released by hypertrophic adipocytes [2].…”
Section: Discussionmentioning
confidence: 94%
“…However, they do not support a strong association between individual or total serum carotenoids and insulin resistance (Blondin et al, 2013), despite the fact that such food intake patterns have been associated with the prevalence of insulin resistance (Liese et al, 2009). In addition, relatively high daily consumption of tomatobased products or lycopene supplements was reported ineffective in reducing conventional CVD risk markers in moderately overweight, healthy, middle-aged individuals (Thies et al, 2012). Future studies should focus on the amelioration of the glycemic profile in order to evaluate the potential effect of tomato juice supplementation on the reduction of the progression of prediabetes to diabetes.…”
Section: Discussionmentioning
confidence: 97%
“…The results reported by Thies et al [102] indicated that a relatively high daily consumption of tomato-based products (equivalent to 32-50 mg lycopene/day) or lycopene supplements (10 mg/day) was ineffective in reducing conventional CVD risk markers in moderately overweight, healthy, middleaged individuals. However, Burton-Freeman et al [103] and Xaplanteris et al [104] showed that consuming tomato products with a meal attenuated postprandial lipemia-induced oxidative stress and the associated inflammatory response.…”
Section: Hypercholesterolemia and Cvdmentioning
confidence: 94%